PEMEROLEHAN POLA KALIMAT BAHASA JAWA ANAK USIA PRASEKOLAH (3âˆ’4 TAHUN) - Endang Sri Maruti (Universitas Negeri Surabaya, 2019)
Preschool age is a golden age in child development, including the development of language. This research focus on the types and patterns of sentences Javanese preschool children in early Childhood Islamiyah Madiun To explain the focus, the researcher used descriptive-qualitative. Data are collected from 12 children by observation and recorded. Data are analized by distributional analysis. The results showed that the sentence form preschoolers including at the level of a simple sentence which declarative, interrogative, and an imperative sentence. The sentence patterns are single sentences and complex sentences.